Enhancing HF/E Outreach Goals Through Multidisciplinary Collaboration. (July 2014) - Proaps, Alexandra B.; Kennedy, Rebecca A.
Past Human Factors and Ergonomics Society (HFES) President Eduardo Salas emphasized how important it is for human factors/ergonomics (HF/E) professionals to embrace other disciplines. As members of the HF/E community, we can reach a wider audience and increase awareness of our discipline by collaborating with others who share our vision for improving human–technology interaction. We interviewed two past recipients of HFES's Oliver Keith Hansen Outreach Award, recognizing service and excellence in outreach in HF/E. Nancy J. Cooke and Ronald G. Shapiro each highlighted areas in which HF/E students and professionals can enhance their outreach efforts through multidisciplinary collaboration.